The Relation of Serum Adipocytokines Levels and Haematological Malignancy - Noor Fadzilah Zulkifli; Nur Syahrina Rahim; Asral Wirda Ahmad Asnawi; Ainul Nadhirah Abdul Razak; Chang Kian Meng (Neoplasia Research, 2024)
Non-Indexed Publication